All-hexahedral element meshing: Automatic elimination of self-intersecting dual lines - Calvo, Nestor Alberto (2002)
There has been some degree of success in all-hexahedral meshing. Standard methods start with the object geometry defined by means of an all-quadrilateral mesh, followed by the use of the combinatorial dual to the mesh in order to define the internal connectivities among elements. For all of the known methods using the dual concept, it is necessary to first prevent or eliminate self-intersecting (SI) dual lines of the given quadrilateral mesh. The relevant features of SI lines are studied, giving a method to remove them, which avoids deforming the original geometry. Some examples of resulting meshes are shown where the current meshing method has been successfully applied.